THEMATIC LEARNING PROCESS BASED ON UPGRADE SCHOOL (UGS) IN SD NEGERI KUTA BAKMEE - Tazkia; Quratul Thahirah; Zahraton syukriah; Miftah hulzanah; Ulfa khoirina; Danil Hamzah; Wahyuni; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses qualitative research methods, namely researching based ondescriptive qualitative at SD Negeri Kuta Bakmee Based on the facts seen in the schoolthat teachers still use old/conventional methods in the thematic learning process .Researchers observed the learning carried out by teachers of SD Negeri Kuta Bakmeethat thematic learning provides opportunities for teacher creativity in the active learningprocess. Through this research method, it will be elaborated with a transcript to produceintegrative thematic learning changes. It is known that the curriculum used in the schoolis still partly in class using an independent learning curriculum so that the learningprocess carried out is quite different and insignificant with the results obtained bystudents in integrative thematic learning. In the ever-evolving world of education,upgrading schools is an important step to prepare students for an increasingly complexfuture. Changes that occurred at SD KUTA BAKMEE BANDA ACEH from the 2013curriculum with an independent curriculum to be creative by grouping themes in onelesson for example about zoos, in that theme there are already several subjects besidesIndonesian, namely Ipas, mathematics. Teachers also use media during the learningprocess to make students understand faster.